Analysis of Factors Influencing the Quality of Nursing Care: Case Study in the Surgical Room - Hendra Harwardi; Fatmawati Fatmawati; Ricco Arika Sandy; Indah Budi Yanti; Aryetmi Aryetmi; Roza Elia (Indonesian Journal of Global Health Research, 2026)
Nursing care quality is an important indicator in assessing healthcare service quality, particularly in surgical wards with high service complexity. Several factors such as competence, supervision, and workload are assumed to influence nursing care quality. This study aimed to analyze factors associated with nursing care quality in the surgical ward at Dr. M. Djamil General Hospital Padang in 2025. This study used an analytic design with a cross-sectional approach. The sample consisted of 96 nurses selected using proportional random sampling. Data were collected using structured s and analyzed using chi-square tests and logistic regression. The validity test showed that all questionnaire items on competence, supervision, workload, and nursing care quality variables were declared valid because the r-count values were higher than the r-table value (0.361). Meanwhile, the reliability test results indicated that all variables had Cronbach’s Alpha values greater than 0.70, meaning that the research instrument was reliable and appropriate for data collection. The results showed that 50% of nursing care quality was categorized as good. Most respondents had good competence (66.7%), good supervision (56.2%), and heavy workload (57.3%). Bivariate analysis showed that supervision and workload were significantly associated with nursing care quality (p < 0.05), while competence was not significantly associated (p = 0.279). Multivariate analysis showed that supervision was the most dominant factor influencing nursing care quality (p = 0.046; OR = 3.03).